2017
DOI: 10.3389/fpls.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis of Apple Leaves in Response to Alternaria alternata Apple Pathotype Infection

Abstract: Alternaria blotch disease of apple (Malus × domestica Borkh.), caused by the apple pathotype of Alternaria alternata, is one of the most serious fungal diseases to affect apples. To develop an understanding of how apples respond to A. alternata apple pathotype (AAAP) infection, we examined the host transcript accumulation over the period between 0 and 72 h post AAAP inoculation. Large-scale gene expression analysis was conducted of the compatible interaction between “Starking Delicious” apple cultivar and AAAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 89 publications
(91 reference statements)
7
78
1
Order By: Relevance
“…Undoubtedly, the work described in this report is in accordance with the recent reports of Di et al (2017) who suggested that the involvement of SA, ETH and JA signaling in tomato toward susceptibility against pathogen infect and Zhu et al (2017) who suggested flavonoid biosynthesis were activated during apple leaves in response to Alternaria alternata apple pathotype infection this process. Our results provide insights on the flavonoid regulation network, which can be used to improve apple tree breeding and strategies for plant rust resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Undoubtedly, the work described in this report is in accordance with the recent reports of Di et al (2017) who suggested that the involvement of SA, ETH and JA signaling in tomato toward susceptibility against pathogen infect and Zhu et al (2017) who suggested flavonoid biosynthesis were activated during apple leaves in response to Alternaria alternata apple pathotype infection this process. Our results provide insights on the flavonoid regulation network, which can be used to improve apple tree breeding and strategies for plant rust resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Apple leaves infected with Alternaria activated flavonoid biosynthesis and the genes involved in phytohormone signaling pathways (ABA, JA, ETH) were upregulated (Zhu et al, 2017). Sugars and hormones can modulate anthocyanin biosynthesis via the coordinated regulation of the R2R3-MYB/bHLH/WD40(MBW) complex (Das et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…447 Other authors observed that upregulation of these genes can be associated with 448 resistance [40,90]. In contrast, phenylpropanoid biosynthesis was enriched at 12 hai in 449 the compatible interaction of an apple cultivar and A. alternata [38]. Furthermore, this 450 pathway was enriched with downregulated genes in cucumber infected by a mutant of 451 hop stunt viroid-grapevine at 28 dai [33].…”
mentioning
confidence: 98%
“…Other studies reported chitinases as 422 primary temporal responses in apple and peach plants infected with Alternaria 423 alternata and Xanthomonas arboricola pv. pruni, respectively [38,99], differentially 424 expressed in coconut infected with phytoplasma [100] and in the cacao-Moniliophthora 425 perniciosa pathosystem [37]. Genes involved in the synthesis of this enzyme were 426 induced first at 1 dai and most prominently at 11 days after the inoculation of wheat 427 susceptible to yellow rust [29].…”
mentioning
confidence: 99%
See 1 more Smart Citation